Biodegradation of aniline - Gheewala, Shabbir H.; Annachhatre, Ajit P.; Umita, Teruyuki; Yang, Byung-Soo; Swedish International Development Authority (Bangkok : Asian Institute of Technology, 1995)
The biodegradability of aniline was tested using the conventional activated sludge process. Aniline was used as the sole carbon source for the mixed microbial community in the activated sludge. The concentrations of aniline were varied from 50 mg/L to 350 mg/Lin steps of 50 mg/L. The aerobic activated sludge unit was operated at ambient temperature and an HRT of 13.33 hours and an SRT of 12 days. Removal efficiencies of 95-100% were obtained even for aniline concentrations upto 350 mg/L with satisfactory subsequent nitrification. Ammonia oxidation rates of 1-4 mg/gML VSS/h were obtained. Batch tests were carried out to test the inhibitory effects of high concentrations of aniline on the microorganisms. The concentrations used in the three batch tests were upto 425 mg/L. The aniline degradation took place very quickly with nitrification picking up as soon as the aniline concentration dropped below about 3-4 mg/L. In the cases when initial concentration of aniline was 250 mg/L and above, complete nitrification did not take place even though the aniline concentration dropped rapidly. The toxicity effect of aniline on the nitrification process was modelled. The model showed that inhibitory effect of aniline was pronounced when aniline concentration exceeded 2 mg/L. Below this concentration, the inhibitory effect of aniline was insignificant.
Thesis (M. Eng.) - Asian Institute of Technology, 1995
A thesis submitted m partial fulfilment of the requirement for the degree of Master of Engineering.
Keywords: Sewage -- Purification -- Activated sludge process